2008
DOI: 10.1093/hmg/ddn095
|View full text |Cite
|
Sign up to set email alerts
|

Functional definition of the mutation cluster region of adenomatous polyposis coli in colorectal tumours

Abstract: The mutation cluster region (MCR) of adenomatous polyposis coli (APC) is located within the central part of the open reading frame, overlapping with the region encoding the 20 amino acid repeats (20R) that are beta-catenin-binding sites. Each mutation in the MCR leads to the synthesis of a truncated APC product expressed in a colorectal tumour. The MCR extends from the 3' border of the first 20R coding region to approximately the middle of the third 20R coding region, reflecting both positive and negative sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(81 citation statements)
references
References 44 publications
1
79
1
Order By: Relevance
“…Drosophila APC2 has five 20Rs ( Figure 1A); however, prior biochemical studies established that 20R2 of human APC does not bind bcat (Liu et al 2006;Kohler et al 2008). Human 20R2 shares considerable sequence identity with other bcat-binding 20Rs, but lacks an upstream acidic residue (Supporting Information, Figure S1) that contacts one of the "charged buttons" in bcat (Ha et al 2004;Xing et al 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drosophila APC2 has five 20Rs ( Figure 1A); however, prior biochemical studies established that 20R2 of human APC does not bind bcat (Liu et al 2006;Kohler et al 2008). Human 20R2 shares considerable sequence identity with other bcat-binding 20Rs, but lacks an upstream acidic residue (Supporting Information, Figure S1) that contacts one of the "charged buttons" in bcat (Ha et al 2004;Xing et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…In designing Drosophila APC2 mutants devoid of particular bcat-binding sites, we were also informed by biochemical work demonstrating that the second 20R of human APC (20R2) lacks any detectable affinity for bcat, even when phosphorylated (Liu et al 2006;Kohler et al 2008). Initially, this finding suggested that 20R2 is a degenerate 20R that lost affinity for bcat through evolution; however, we recently showed that 20R2 is highly conserved in species as diverse as sea snails (Lottia gigantean), fruit flies, and humans (Roberts et al 2011).…”
mentioning
confidence: 99%
“…A novel truncation mutation G1288* in APC was also detected in 48 (84%) cells in the major clone. The mutation site was in close proximity to the "mutation cluster region" (codon 1300), in which truncation mutations have been shown to abrogate the β-catenin-binding activity of APC [21]. When we assessed the landscape at an individual-cell level within the single tumor tissue, we found that only a few genes (13/186 = ~7.0%) were shared with the cohort results.…”
Section: Identification Of Cancer Driver Genesmentioning
confidence: 90%
“…DNA Constructs, siRNAs, and Morpholinos-The following constructs have been described previously: pcDNA-FLAGAmer2, pEGFP-Amer2, pcDNA-FLAG-Amer1, pEGFP-APCArmadillo (Arm), and pEGFP-APC-Arm-N507K (3); pCMV-APC, monomeric YFP (mYFP)-APC, mYFP-␤-catenin, mYFPaxin, mYFP-conductin, and monomeric red fluorescent protein-dominant-active LRP6 (10); pcDNA3.1-FLAG (11); and mYFP-APC1641 (12). To generate mYFP-␤-catenin S33Y, point mutations were introduced into YFP-␤-catenin by PCR.…”
Section: Methodsmentioning
confidence: 99%